Public transport services in Kota Kinabalu : an assessment by QUALBUS model / Florence Wong @ Florence Francis - Wong @ Francis, Florence (2012)
Bus services can be considered as the cheapest public transportation modes. The services should be expanded in order to make it competitive with other land public transport. This study entitled, "Public transport services in Kota Kinabalu : An assessment by QUALBUS model" was conducted among customers of city bus services in Kota Kinabalu City. The purpose of the research is to determine the satisfaction of customers towards the five dimensions of service quality as well as to determine the relationships between the five dimensions of service quality with customer satisfaction. This study used a descriptive and quantitative approach with survey method to gather information. A total of 370 respondents were selected using convenience sampling to fill up the questionnaires. The questionnaire was developed based on QUALBUS scale that was used in previous researches (Eboli and Mazulla, 2007; Muthupandian & Vijayakumar, 2012; Perez et at, 2007; Tan et al., 2012). The result of the study showed that the overall customer satisfaction for public buses services is low. Satisfaction for reliability and receptivity was also low but for assurance, empathy and tangibility satisfaction was moderate. All of the dimensions of service quality: tangibility, reliability, receptivity, assurance and empathy were significantly correlated to customer satisfaction. This study proposed that further research should include other routes of the public buses in Kota Kinabalu City so that a more comprehensive understanding of the public buses service quality is attained.